Kemp’s authenticity model: A convergence point for conservation-restoration practice - Calderon, Ryan Miguel R. (Animo Repository, 2024)
Art conservation-restoration approaches have been discussed by philosophers in the field of aesthetics. Debates aim to address the need for a process that protects art from damage and decay. Purism is a restoration process that prohibits intervention in artworks other than the artist itself, for doing so will compromise the integrity of the art object and its aesthetic value. A purist restoration merely aims to clean an artwork or reattach original pieces had a work been damaged. Integral restoration, on the other hand, allows the integration of new materials and aims to restore an object to its pre-damaged state. Purism views authenticity as a necessary condition of aesthetic value and renders the original materials of the art irreplaceable. Because purists regard integral repair as a provision of unoriginal parts to a work, it cannot produce appropriate objects of aesthetic value. Integralists would say that restoration aims to revive the lost aesthetic value from damage and value the completeness of appearance whether authenticity is jeopardized. In this paper, I claimed that a dynamic view on authenticity resolves the disparity between purism and integral restoration. Here, I used Kemp’s authenticity model as a framework to demonstrate how changing variables in an object’s authenticity determine its aesthetic value. I offered two arguments to address the contention between both conservation-restoration approaches. The first one stated that the authenticity of art objects that have undergone conservation-restoration changes. The second argument stated that the aesthetic value is contingent on changes in authenticity. I aimed to provide a synthesis to both theories by addressing the purist’s contention against integral restoration, and legitimize both methods by understanding considerations on their authenticity and their effects on the aesthetic value.